The Effect of Transformational Leadership Values on Worker Performance - Irfansyah; Perdana, Mirwan Surya (Research Horizon, 2025)
The performance of banking credit in the consumer sector, particularly in property loans, has shown significant improvement in line with the post-pandemic economic recovery. This growth fosters optimism for the consumer business, as reflected by the rising demand for both commercial and FLPP housing each year. The increasing trend in property demand highlights the sector's sustainable growth potential, bolstered by government policies such as tax incentives for property purchases and FLPP housing development programs. Consequently, the opportunity for consumer credit expansion in the Regional Office area is substantial. Additionally, consumer credit significantly enhances the Yogyakarta Regional Office’s performance, given its relatively low non-performing loan (NPL) risk. However, challenges remain in consumer loan marketing, with the KPR achievement rate at 93.01% still below optimal levels. Similarly, as of October 2024, key metrics such as Special Attention Debtors (DPK) and NPL have yet to meet the current year’s RKAP targets. This study aims to examine the impact of transformational leadership on employee performance, focusing on Relationship Managers (RMs) and RM KPP within the Yogyakarta Regional Office. It explores how transformational leadership values—such as inspirational motivation, personal development, and empowerment—affect RMs’ productivity and efficiency in meeting consumer business performance goals. A mixed-methods approach combining surveys and interviews is utilized to gather data from KPP RMs in the Yogyakarta Regional Office, using instruments that assess perceptions of leadership style and its correlation with performance. The findings are expected to offer practical insights for designing leadership training programs to enhance team performance by implementing transformational leadership principles. Furthermore, the study aims to provide recommendations for the banking industry on developing effective leadership strategies to boost consumer credit growth and overall productivity in the Yogyakarta Regional Office.